2019
DOI: 10.1590/1981-6723.26518
|View full text |Cite
|
Sign up to set email alerts
|

Cardanols detected in non-polar propolis extracts from Scaptotrigona aff. postica (Hymenoptera, Apidae, Meliponini)

Abstract: The propolis produced by stingless bees of the tribe Meliponini is a viscous product that contains the resin collected from buds, leaves and plant exudates, mixed with salivary secretions, wax and soil. The species Scaptotrigona aff. postica (Latreille, 1807), (Hymenoptera, Apidae, Meliponinae) popularly known as “tubi” in Maranhão State, Brazil, does not mix soil to produce its propolis. The propolis from S. postica harvested in Barra do Corda, Maranhão State, is popularly used in the treatment of wounds and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 77 publications
0
15
0
Order By: Relevance
“…The mass spectra of compound 76 (Figure 1e) and 88 in positive ionization mode, exhibited base peak ion at m/z 111 produced by simple benzylic cleavage, while the resorcinols 72, 82, and 89 exhibited base peak ions at m/z 123, corresponding to the dihydroxytropylium ion also originated by simple benzylic cleavage. 16,[53][54][55]…”
Section: Chalconesmentioning
confidence: 99%
See 2 more Smart Citations
“…The mass spectra of compound 76 (Figure 1e) and 88 in positive ionization mode, exhibited base peak ion at m/z 111 produced by simple benzylic cleavage, while the resorcinols 72, 82, and 89 exhibited base peak ions at m/z 123, corresponding to the dihydroxytropylium ion also originated by simple benzylic cleavage. 16,[53][54][55]…”
Section: Chalconesmentioning
confidence: 99%
“…postica from Barra do Corda. 16 Mango fruits are suggested as important resin source also for honeybee propolis in tropical habitats. 54 Differences in cycloartane-type triterpenoids may occur in meliponine propolis from distinct tropical regions, which has been attributed to differences in the varieties of mango fruit trees cultivated in one country or locality and another.…”
Section: Hypotheses About Plant Origins Of the Constituentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studying propolis, some authors have found the abovementioned cycloartanes (but not any phenolic lipids), and based on these findings they concluded that Mangifera indica L. was the main plant source of the studied samples [ 1 , 8 , 13 , 14 ]. Others have identified only the cardols, no cycloartane acids, and made the same conclusion [ 4 , 15 ]. In these cases, the respective compounds have been isolated, purified and identified by spectral methods.…”
Section: Introductionmentioning
confidence: 57%
“…These are phenols that are unsubstituted at the 4-position (NCBI, 2021c). NEGRI et al (2019), reported this compound among the main constituents identified as unsaturated cardanols, in hexane extract from the Scaptotrigona aff. postica geopropolis.…”
Section: Chemical Composition Of Propolismentioning
confidence: 98%